Proposta de melhoria no processo de geração de relatórios através do Lean Office para o setor de operações de um banco - Cremonezi, Flavio Luiz (2024)
The services sector plays a crucial role in the global economy, being fundamental in several regions of the world. One of its distinctive features is the direct contact with the end customer, which directly impacts the quality of the service and, therefore, customer satisfaction. The banking industry is marked by intense interaction between customers and service providers. Customer satisfaction in this sector is achieved through constant improvement in the quality of services offered. The main challenges faced by banks include agility, quality and efficiency, interconnected factors that play great importance in determining the quality of banking services. In this context, this study focused on analyzing the process of generating the “Relatório de Circularização” in a banking institution and sought to introduce the principles of Lean Office in a bank. The research, of a qualitative and exploratory nature, aimed to propose and implement improvements in the institution's "back office" processes, using the concepts of continuous improvement, such as Lean and Lean Office, through the process management methodology. The data collected was thoroughly analyzed, and the results highlighted the need for improvements in the process, aiming to increase the level of customer satisfaction. Through brainstorming, main problems in the process were identified, and mapping was carried out using the SIPOC and VSM. The work proposed some suggestions for improving the process. Although the improvements were not implemented during the study, the TO-BE process model was designed to demonstrate how the process would work after the improvements were implemented, including cycle time estimates for fulfilling the request. These changes would also result in a reduction in the cost per report issued, providing an annual economic return for the institution.